Evaluation of Navigation in Immersive Large-Scale VR Environments Using Minimap-assisted Teleportation - Domenico, Gabriel Di; Becker, Felipe Da Cas; Schirmer, Bento Borges; Berwaldt, Natan Luiz Paetzhold; Freitas, Gustavo Machado de; Cossetin Neto, Alfredo; Pozzer, Cesar Tadeu; Fontoura, Lisandra Manzoni; Nunes, Raul Ceretta (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
In virtual reality (VR), large-scale applications present numerous challenges in navigation that must be addressed. Providing users with the freedom to move anywhere at any time is crucial for delivering an optimal immersive experience, particularly in large-scale environments. This paper evaluates the use of 2D minimaps for orientation and locomotion, with the goal of enhancing user navigation efficiency and precision. We discuss various methods for representing terrain information within a 2D panel, incorporating both real-world data and in-game elements to recreate 3D terrains accurately. An empirical user study involving 24 participants evaluated three teleportation techniques: the World in Miniature (WIM), the WIM in a 2D panel, and the 2D minimap. Metrics such as completion time, teleportation steps, and user workload indicated that 2D minimaps significantly improve navigation efficiency. Considering the time of completion, the 2D representation had a difference of 23.12% compared with WIM implementations. Additionally, considering the number of teleportation steps taken, the usage of a minimap proved more precise with a considerable difference of 138.65% compared to the WIM technique, leading to reduced task completion times and teleportation steps.